He "look" honest - big white thief - V. Kerruish; J. Purdy (Law Text Culture, 1998)
Our title is taken from a poem, 'Chained', by the Aboriginal author and activist Kevin Gilbert (1990: 38). The poem gives expression to a contradiction of 'white man law' in Australia: Pinchim wimmen, pinchim land Kill the Blackmen, whiteman grand Him make law for whiteman good Him steal land and Blackman food